2020
DOI: 10.1186/s12911-020-01215-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of risk factors for patients with diabetes: diabetic polyneuropathy case study

Abstract: Background: Methods of data mining and analytics can be efficiently applied in medicine to develop models that use patient-specific data to predict the development of diabetic polyneuropathy. However, there is room for improvement in the accuracy of predictive models. Existing studies of diabetes polyneuropathy considered a limited number of predictors in one study to enable a comparison of efficiency of different machine learning methods with different predictors to find the most efficient one. The purpose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…They concluded that ANN provides a better performance obtaining 89.88% of Area Under the Curve. Likewise, Metsker et al [ 14 ] developed a structured procedure for predictive modeling, which includes data extraction, pre-processing, model adjustment, performance, and selection of the best models. The dataset comprises information about 5846 patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that ANN provides a better performance obtaining 89.88% of Area Under the Curve. Likewise, Metsker et al [ 14 ] developed a structured procedure for predictive modeling, which includes data extraction, pre-processing, model adjustment, performance, and selection of the best models. The dataset comprises information about 5846 patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…In Reference [ 60 ], Metsker et al tackled the problem of predicting the risk of polyneuropathy in diabetic patients. To find the best way to handle missing data, they chose different solutions and obtained six different datasets.…”
Section: Resultsmentioning
confidence: 99%
“…Among the best models, those in the Ensemble family (e.g., XGB, GBT) were chosen both for their medium–high performance [ 21 , 30 , 32 , 33 , 44 , 51 , 58 , 61 ] and their training speed. Models in the DL family [ 27 , 35 , 37 , 49 , 52 , 53 , 60 ], especially RNN and ANN, have been increasingly chosen in recent years. The advantage of these systems is their potential in terms of performance, although the resources (time and the amount of data) required for training are reported to be higher for DL models than traditional ML models.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no standardized decision-making algorithm for DSPN diagnosis, HbA1c qualifies as an important diagnostic criterion for DPSN because HbA1c a major risk factor for microvascular complications and closely associated with DSPN in T2DM [ 64 ] The neutrophil-lymphocyte ratio is an inflammatory marker and an important factor that predicts cardiovascular disease [ 65 ] and foot ulcer infection [ 66 ] in diabetic patients. Neutrophil level was also the most sensitive node for decision making of DPSN prediction in a previous study [ 67 ], and higher neutrophil-lymphocyte ratio might be related to chronic inflammatory process and increase the risk of DSPN [ 68 ].…”
Section: Discussionmentioning
confidence: 99%